Chemotaxonomy in some Mediterranean plants and implications for fossil biomarker records. (15th December 2017) - Norström, Elin; Katrantsiotis, Christos; Smittenberg, Rienk H.; Kouli, Katerina
Abstract: The increasing utilization of n -alkanes as plant-derived paleo-environmental proxies calls for improved chemotaxonomic control of the modern flora in order to calibrate fossil sediment records to modern analogues. Several recent studies have investigated long-chain n -alkane concentrations and chain-length distributions in species from various vegetation biomes, but up to date, the Mediterranean flora is relatively unexplored in this respect. Here, we analyse the n -alkane concentrations and chain-length distributions in some of the most common species of the modern macchia and phrygana vegetation in south western Peloponnese, Greece. We show that the drought adapted phrygana herbs and shrubs, as well as some of the sclerophyll and gymnosperm macchia components, produce high concentrations of n -alkanes, on average more than double n -alkane production in local wetland reed vegetation. Furthermore, the chain-length distribution in the analysed plants is related to plant functionality, with longer chain lengths associated with higher drought adaptive capacities, probably as a response to long-term evolutionary processes in a moisture limited environment. Furthermore, species with relatively higher average chain lengths (ACL) showed more enriched carbon isotope composition in their tissues (δ 13 Cplant ), suggesting a dual imprint from both physiological and biochemical drought adaptation. The findings have bearings on interpretation of fossil sedimentary biomarker records in the Mediterranean region, which is discussed in relation to a case study from Agios Floros fen, Messenian plain, Peloponnese. The 6000 year long n -alkane record from Agios Floros (ACL, δ 13 Cwax ) is linked to the modern analogue and then evaluated through a comparison with other regional-wide as well as local climate and vegetation proxy-data. The high concentration of long chain n -alkanes in phrygana vegetation suggests a dominating imprint from this vegetation type in sedimentary archives from this ecotone.